2020
DOI: 10.1002/jgh3.12324
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and renal changes in patients with chronic hepatitis C infection after hepatitis C virus clearance by direct‐acting antivirals

Abstract: Background and Aim The impact of hepatitis C virus (HCV) clearance by direct‐acting antiviral agents (DAAs) on HCV‐related extrahepatic manifestations is not well known. We evaluated the effect of viral clearance on metabolic and renal parameters. Methods In this prospective study, HCV patients who achieved a sustained virologic response (SVR) by DAAs were evaluated before, at the end, and 24 weeks after treatment for glycemic (serum glucose and insulin, HOMA‐IR, HOMA‐β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…Recently, we showed that HCV clearance by DAAs either reversed or improved IR by up to 90%, 13 reduced serum glucose levels and, in more than 30% of people with impaired fasting glucose, normalized their serum glucose values 27 . In addition, it has been reported that HCV clearance by DAAs is associated with improved glycaemic control in people with diabetes, as shown by lower mean HbA1c levels and reduced insulin use 28 …”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Recently, we showed that HCV clearance by DAAs either reversed or improved IR by up to 90%, 13 reduced serum glucose levels and, in more than 30% of people with impaired fasting glucose, normalized their serum glucose values 27 . In addition, it has been reported that HCV clearance by DAAs is associated with improved glycaemic control in people with diabetes, as shown by lower mean HbA1c levels and reduced insulin use 28 …”
Section: Discussionmentioning
confidence: 98%
“…[24][25][26] Recently, we showed that HCV clearance by DAAs either reversed or improved IR by up to 90%, 13 reduced serum glucose levels and, in more than 30% of people with impaired fasting glucose, normalized their serum glucose values. 27 In addition, it has been reported that HCV clearance by DAAs is associated with improved glycaemic control in people with diabetes, as shown by lower mean HbA1c levels and reduced insulin use. 28 Our findings thus confirm that HCV clearance by DAAs either reverses or improves IR and insulin sensitivity, whilst reducing pancreatic β-cell distress, thus confirming that HCV clearance by DAAs restores HCV-impaired insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This viral hypolipidaemia is typically manifested by lower levels of LDL-C and total cholesterol in comparison with non-infected individuals while levels of HDL-C and triglycerides remain unaffected ( Drazilova et al, 2018 ). Recent studies reported rapid changes in serum lipid levels during DAA based therapy manifested as an increase in LDL concentration and in total cholesterol, with no effect on HDL cholesterol levels ( Hashimoto et al, 2016 ; Nevola et al, 2020 ). Further, during the 24 months follow-up period after the DAA treatment, a significant reduction of apoB serum values, a direct marker of LDL-C, was observed ( Gitto et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%